Differential effects of size-specific particulate matter on the number of visits to outpatient fever clinics: A time-series analysis in Zhuhai, China - Li, Duo; He, Rui; Liu, Peixin; Jiang, Hong (Frontiers in Public Health, 2022)
While many studies have investigated the adverse effects of particulate matter (PM), few of them distinguished the different effects of PM2.5, PM10, and coarse PM (PMc) on fever clinic visits. Our study aimed to estimate and compare the acute, cumulative effects of the exposure to three size-specific particles on the number of visits to outpatient fever clinics. To examine the association between daily PM concentrations and outpatients in fever clinics, a generalized additive Poisson model was applied, stratified by sex, age and season. Our study included 56144 outpatient visits in Zhuhai, from Jan 2020 to June 2021. On the current day, each 10 mg/m3 increment of PM10 and PMc were estimated to increase fever clinic visits by 1.74% (95% CI, 0.59%, 2.91%) and 4.42 % (2.30%, 6.58%), respectively. Cumulative effects enhanced from lag01-lag05 for PM10 and PMc, and PMc had the strongest impact (ER= 8.92% (5.91%, 12.01%) at lag05). Females and outpatients of age 14 years and above increased the PM-related risk. During the cold season, significant effects could all be observed for the three-size PM, while only PMc showed the impact during the warm season. Overall, the three size-specific PM exerted different effects on the fever clinic visits. Strategies to control the concentrations of PM are still necessary, especially against PM10 and PMc.